Desain dan Simulasi Monitoring Suhu dan Kelembaban pada Peternakan Menggunakan Server Terpusat - Yuwono Marta Dinata (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Indonesia is the largest archipelagic country with a variety of natural resources owned. One of them is animal husbandry, especially dairy cows, the number increases with the passage of time. Therefore, good management is needed to produce the best dairy products, cows should not be stressed. So it is necessary to make a comfortable place with temperature and humidity conditions that are in accordance with the recommended temperature conditions of 5ºC – 25ºC. So that through literature studies, looking at existing problems, then designing for a temperature and humidity monitoring system with a centralized server system is carried out. Several temperature sensors, humidity sensors and fans are placed in each cage. Then to support the security of the cage is placed an RFID Reader for access to the cage controlled by the MCU. In addition, a web-camera is also installed that will notify the owner if any unwanted object is detected by the motion sensor online. These designs and simulations have been successfully carried out and created, with some suggestions for subsequent researchers for the development of automatic systems of feed givers and cage cleaners.